The Prieto-Gil Robles meeting of October 1947 : Britain and the failure of the Spanish anti-Franco Coalition, 1945-50 / David J. Dunthorn - Dunthorn, David J. (David Joseph)
En : European History Quaterly, vol.30(1), 200-?